Optimization of Tractor Tire Tread Structure Using Finite Element Method (Aintelia Science Notes, 2023)
In this study, the tractor tire used for the field was modeled using the Visual Media Finite Element Analysis (FEA) technique and the tire life of this model was tried to be estimated by using the ANSYS software. Mooney-Rivlin was chosen as the tire material because it is a material with high elasticity and behaves in accordance with the mechanics and behavior of the rubber used in tires. The wheel model is modeled as solid, consisting of Solid186 elements.
Keywords: Mooney-Rivlin; Optimization; Finite Elements; Tractor